AB0624 High correlation between a new ultrasonic method for spinal densitometry and dual x-ray absorptiometry. (23rd January 2014) - Muratore, M.; Conversano, F.; Casciaro, E.; Soloperto, G.; Franchini, R.; Greco, A.; Quarta, E.; Grimaldi, A.; Casciaro, S.
Abstract : Background: Osteoporosis is a systemic skeletal disease characterized by low bone mass and microarchitectural deterioration of bone tissue leading to increased fragility and augmented fracture risk. Bone densitometry performed through dual X-ray absorptiometry (DXA) provides quantitative measurements of bone mineral density (BMD) and such measurements currently represent the reference indicated by World Health Organization for osteoporosis diagnosis. The most frequently investigated anatomical sites are lumbar spine and proximal femur, since it has been demonstrated that BMD measurements on these sites are the most reliable to predict the global fracture risk. Spinal DXA, in particular, is the preferred technique for temporal monitoring of BMD variations. However, DXA examinations exploit X-rays and for this reason they cannot be used for population mass screenings aimed at providing early osteoporosis diagnosis. Objectives: Aim of this work is to perform a preliminary clinical validation of a new technique for spinal bone densitometry, which does not require ionizing radiation but employs only ultrasound (US) signals. Methods: A total of 280 female patients were recruited for this study according to the following criteria: 45-75 years of age, body mass index (BMI) ≤ 40 kg/m 2, absence of significant deambulation impairments, medical prescription for a spinal DXA, signed informed consent. All the enrolled patients underwent two different diagnostic examinations: a conventional spinal DXA (Hologic Discovery) and an US scan of lumbar spine, acquiring both echographic images and unfiltered "raw" signals. US data were analyzed through a new algorithm that performed a series of spectral and statistical analyses, involving both the echographic images and the corresponding unfiltered "raw" US signals, and provided as final output the same diagnostic parameters obtained from a DXA examination (BMD, T-score, Z-score). Accuracy of each parameter calculated by this algorithm was then evaluated through a direct comparison with DXA results as a function of both patient age and BMI. Results: For 86.1% of the studied patients US diagnosis (healthy, osteopenic or osteoporotic patient) was the same of the corresponding DXA one. In particular, diagnostic accuracy was 86.7% for patients with BMI<25 kg/m 2 (n=158), 89.2% for those with BMI in the range 25-30 kg/m 2 (n=83) and 76.9% for those with BMI in the range 30-40 kg/m 2 (n=39). Assessing diagnostic accuracy as a function of patient age, we obtained the following results: 84.1% for patients in the age range 45-55 yr (n=69), 87.5% in 56-65 yr (n=160), 84.3% in 66-75 yr (n=51). For each group of patients having both BMI and age in the same ranges, Pearson correlation coefficient (r) between DXA and US results was calculated for each diagnostic parameter (BMD, T-score, Z-score): all the obtained values were in the range 0.67-0.88 (p<0.001) and their trends against BMI and age qualitatively resembled the reported diagnostic accuracy trends. Conclusions: The proposed method represents the first US technique for BMD assessment directly on spine. Reported results showed an unprecedented agreement between DXA and US diagnosis and are therefore encouraging in view of future applications of this method for early diagnosis of osteoporosis and therapeutic monitoring. Acknowledgements: This work was partially funded by FESR P.O. Apulia Region 2007-2013 – Action 1.2.4, grant n. 3Q5AX31. Disclosure of Interest: M. Muratore: None Declared, F. Conversano Shareholder of: Echolight srl, a National Research Council spin-off that may or may not benefit from results of this study, E. Casciaro Shareholder of: Echolight srl, a National Research Council spin-off that may or may not benefit from results of this study, G. Soloperto: None Declared, R. Franchini: None Declared, A. Greco: None Declared, E. Quarta: None Declared, A. Grimaldi: None Declared, S. Casciaro Shareholder of: Echolight srl, a National Research Council spin-off that may or may not benefit from results of this study